Effect of Perceived Stress on Sleep Quality and Nutritional Status in Professional Female Basketball Players - Beril Köse; Neslihan Çetin (Pamukkale Spor Bilimleri Dergisi)
Athletes face not only physical strength but also intense psychological stress that leads to sleep problems. It is known that one way to manage stress is to make changes in food intake. This study examined the relationship between perceived stress levels, sleep quality, and nutritional status in professional women basketball players. Eighty adult professional women basketball players (age ≥ 19) in the competitive season competing in the Women's Basketball Super League and the lower league Women's Basketball League affiliated with the Turkish Basketball Federation participated in the study. The survey included player characteristics, anthropometric measurements, food consumption frequency, Perceived Stress Scale (PSS-10), and Pittsburgh Sleep Quality Index (PSQI) sections. The mean score of the basketball players participating in the survey from PSS-10 was 19.3±6.66. The perceived stress level and perception of stress discomfort were significantly higher in the women's league (p